BMPER Ameliorates Renal Fibrosis by Inhibiting Tubular Dedifferentiation and Fibroblast Activation - Xie, Ting; Xia, Zunen; Wang, Wei; Zhou, Xiangjun; Xu, Changgeng (Frontiers in Cell and Developmental Biology, 2021)
Tubulointerstitial fibrosis is both a pathological manifestation of chronic kidney disease and a driver for the progress of kidney disease. A previous study has shown that bone morphogenetic protein endothelial cell precursor-derived regulator (BMPER) in involved in lung fibrogenesis. However, the role of BMPER in renal fibrosis remains unknown. In the present study, expression of BMPER was examined by real-time PCR, western blot and immunohistochemical staining. The in vitro effects of BMPER on tubular dedifferentiation and myofibroblast activation were analyzed in cultured HK-2 and NRK-49F cells. The in vivo effects of BMPER were dissected in unilateral ureteral obstruction (UUO) mice by delivery of BMPER gene via systemic administration of plasmid vector. We reported that the expression of BMPER decreased in the kidneys of UUO mice and HK-2 cells. TGF-β1 increased inhibitor of differentiation-1 (Id-1) and induced epithelial mesenchymal transition in HK-2 cells, and knockdown of BMPER aggravated Id-1 upregulation, E-cadherin loss, and tubular dedifferentiation. On the contrary, exogenous BMPER inhibited Id-1 upregulation, prevented E-cadherin loss and tubular dedifferentiation. In addition, exogenous BMPER suppressed fibroblast activation by hindering Erk1/2 phosphorylation. Knockdown of low-density lipoprotein receptor-related protein 1 abolished the inhibitory effect of BMPER on Erk1/2 phosphorylation and fibroblast activation. Moreover, delivery of BMPER gene improved renal tubular damage and interstitial fibrosis. Therefore, BMPER is downregulated in UUO mice and HK-2 cells, and inhibits TGF-β1-induced tubular dedifferentiation and fibroblast activation. Exogenous BMPER inhibits renal fibrosis and may hold therapeutic potential.